Study on Seepage of Coalbed Methane in Pore-fracture Double - porosity Medium - Xing, Liru (International Journal of Natural Resources and Environmental Studies, 2024)
The study of coalbed methane (CBM) seepage within dual-porosity medium constitutes a significant research endeavor in the field of geology and coalbed methane reservoir engineering. This research delves into the complex dynamics governing CBM flow through porous coal matrices within dual-porosity systems. Employing advanced methodologies including numerical simulation and experimental analysis, this investigation aims to elucidate the mechanisms underlying CBM migration, encompassing diffusion and adsorption phenomena within the coal matrix, as well as interactions with adjacent strata. The outcomes of this study carry substantial implications for optimizing CBM extraction techniques and promoting the sustainable utilization of this invaluable natural resource.